Religion, Education, and Maintaining Ethno-religious Harmony in Sanggau, West Kalimantan - Ruslan, Ismail; Amri, Faizal; Yusriadi, Yusriadi (Dinamika Ilmu, 2024)
This study aims to explore the role of religion and education in maintaining inter-ethnic harmony in Sanggau, West Kalimantan, Indonesia. Sanggau, with its ethnic diversity including Malays, Dayaks, Chinese and others, provides a rich context for understanding how inter-group harmony can be maintained through religious and educational interventions. This study uses qualitative methods, including in-depth interviews with religious leaders, community leaders and teacher, as well as observation and documentation of religious, educational and social activities in Sanggau. The data is then recorded and assigned a code. It is subsequently grouped according to broader categories, with reference to the purpose of the research. The relationship between the themes within the data is then narrated in order to facilitate the construction of research conclusions. These conclusions are then associated with the results of previous studies and relevant theories. The findings of this study indicate that small-scale conflicts over religious issues are common in the Sanggau. The conflict arose because of the multi-religious and multi-ethnic situation. Conflicts arose over the construction of places of worship, religious changes and interfaith marriages. However, these conflicts have been resolved through ethno-religious and educational approaches. Group identity is used to strengthen the bonds of fraternity, as expressed in the phrase "kita menyadi’ (we are brothers)". A shared identity is built on the traces of origin, history and the values of local wisdom that are inherited. Local initiatives have also emerged to promote ingroup cooperation through religion and education, successfully cultivating the values of tolerance as the key to maintaining harmony. Religious approaches have given way to ethnic approaches, and education has been part of strengthening narratives of togetherness and peace. Joint religious activities, such as the celebration of religious holidays and inclusive education programmes involving students from different ethnic backgrounds, have proven effective in strengthening solidarity and mutual understanding.